2011
DOI: 10.1016/j.virol.2011.02.016
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 entry inhibition by small-molecule CCR5 antagonists: A combined molecular modeling and mutant study using a high-throughput assay

Abstract: Based on the attrition rate of CCR5 small molecule antagonists in the clinic the discovery and development of next generation antagonists with an improved pharmacology and safety profile is necessary. Herein, we describe a combined molecular modeling, CCR5-mediated cell fusion, and receptor site-directed mutagenesis approach to study the molecular interactions of six structurally diverse compounds (aplaviroc, maraviroc, vicriviroc, TAK-779, SCH-C and a benzyloxycarbonyl-aminopiperidin-1-yl-butane derivative) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 59 publications
3
38
0
Order By: Relevance
“…In fact, the position of the C-␤ atom of Y108 suggests that it is indeed located close enough to VVC for an interaction to be possible. In previous mutagenesis-based studies, the residues identified as interacting with VVC and MVC were similar to those predicted by our models, although there were subtle differences in the extent and nature of the interactions of the two inhibitors with individual residues (45)(46)(47). Overall, MVC and VVC are predicted to have a common binding site within the TM bundle and to contact similar residues, albeit with perhaps some differences in their modes of binding.…”
Section: Affinity Of Vvc For G-protein-coupled and Uncoupled Receptorssupporting
confidence: 75%
See 1 more Smart Citation
“…In fact, the position of the C-␤ atom of Y108 suggests that it is indeed located close enough to VVC for an interaction to be possible. In previous mutagenesis-based studies, the residues identified as interacting with VVC and MVC were similar to those predicted by our models, although there were subtle differences in the extent and nature of the interactions of the two inhibitors with individual residues (45)(46)(47). Overall, MVC and VVC are predicted to have a common binding site within the TM bundle and to contact similar residues, albeit with perhaps some differences in their modes of binding.…”
Section: Affinity Of Vvc For G-protein-coupled and Uncoupled Receptorssupporting
confidence: 75%
“…However, there must be inhibitor-specific conformational changes in the more flexible extracellular loop structures, given the variation in binding of ECLspecific MAbs to CCR5 complexes with different small-molecule inhibitors (43). Having said that, the MAb-binding profiles of MVC-CCR5 and VVC-CCR5 complexes were very similar to one another, although both were different from CCR5 complexes with other small-molecule inhibitors, such as aplaviroc (APL) (45). These inhibitor-specific conformational changes in the ECLs are, however, still sufficient to influence the cross-resistance profiles of MVC-versus VVC-selected viruses (8)(9)(10)43).…”
Section: Discussionmentioning
confidence: 99%
“…For example, although the small-molecule inhibitor maraviroc is thought to interact with residues in CCR5 TM domains 2, 3, and 7 (15,26), our results suggest that TM5 should also be considered in inhibitor design. Indeed, other studies have demonstrated that residues in TM5 play an important role in stabilizing an HIV-resistant conformation of CCR5 that is recognized by small-molecule inhibitors (5,15).…”
Section: Discussionmentioning
confidence: 90%
“…125 I-RANTES Ligand Binding Assay-The 125 I-RANTES binding assay was performed with membranes prepared from HEK293F cells expressing wild-type CCR5 or mutant CCR5 as described previously (22). Briefly, membranes were incubated with 125 I-RANTES (50 l of 50 pM; specific activity, 2,200 Ci/mmol) and compound over a concentration range of 1 ϫ 10 Ϫ5 -6.4 ϫ 10 Ϫ10 M (final assay volume, 150 l) for 45 min at room temperature.…”
Section: Construction Of Plasmids Encoding Wild-type Human Andmentioning
confidence: 99%